Changes of Soil Properties on Various Ages of Rubber Trees in Dhamasraya, West Sumatra, Indonesia - Syafrimen Yasin; . Adrinal; . Junaidi; Erick Wahyudi; Silvia Herlena; . Darmawan (JOURNAL OF TROPICAL SOILS, 2010)
Changes of Soil Properties on Various Ages of Rubber Trees in Dhamasraya, West Sumatra, Indonesia (S Yasin, Adrinal, Junaidi, E Wahyudi, S Herlena and Darmawan): Although rubber has been planted in Indonesia from Holland era, but there is little information about the effect of rubber plantation on the rate of land degradation in Indonesia.  In order to examine the effect of rubber tree (Hevea brasiliansis) ages on land degradation status, a series experiment was done in Dhamasraya district as the main contributor of natural rubber in West Sumatra, Indonesia. Study site divide  into forest (A), crab grass (B), and rubber plantation with ages ranged from 1 (C), 5 (D), 10 (E), 15 (F) and 20 (G) years were selected as study sites and soil samples had been taken from each site, where forest soil  was used as a control. The result proved that the age of rubber tree has strongly affected physical and chemical properties of soil. Organic carbon and total nitrogen content decreased from 3.02%, 2.66%, 1.96%, in site A, B and C, and then increased to 2.33% and 2.49% in site D and E, respectively. This result was opposed with bulk density (BD) value of each site. The highest BD found in site C (1.26 g cm-3), followed by site D, E, B and A with 1.24, 1.14, 1.12 and 0.88 g cm-3, respectively. The similar pattern was also found for selected chemical properties of soil. Soil pH, available phosphorous, exchangeable base cations, cation exchange capacity and base saturation was likely to decrease from 1 to 10 years old plantation and then increased close the natural condition (reflected by forest soil) at 20 years old rubber tree. Since most of plantation was conversed from natural forest, this phenomenon might be because of contribution of organic matter from original condition and addition of fertilizer at the beginning of plantation establishment.